2013
DOI: 10.1227/neu.0b013e31827d1012
|View full text |Cite
|
Sign up to set email alerts
|

Vessel Wall Magnetic Resonance Imaging Identifies the Site of Rupture in Patients With Multiple Intracranial Aneurysms

Abstract: High-resolution MR-VWI identified the site of rupture in patients with aneurysmal SAH, including those patients harboring multiple intracranial aneurysms. It may represent a useful tool in the investigation of aneurysmal SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
116
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(122 citation statements)
references
References 19 publications
0
116
1
1
Order By: Relevance
“…2 Gadolinium enhancement of the walls of ruptured but not unruptured aneurysms on MRI is supportive of wall inflammation. 8 Hoh et al also found capillaries, however, which appears to be a novel observation in small aneurysms, although the photomicrographs provided here are not that clear to me. Large and giant aneurysms certainly can have capillaries or vasa vasorum, although the average size of aneurysms in this series was approximately 8 mm.…”
contrasting
confidence: 46%
“…2 Gadolinium enhancement of the walls of ruptured but not unruptured aneurysms on MRI is supportive of wall inflammation. 8 Hoh et al also found capillaries, however, which appears to be a novel observation in small aneurysms, although the photomicrographs provided here are not that clear to me. Large and giant aneurysms certainly can have capillaries or vasa vasorum, although the average size of aneurysms in this series was approximately 8 mm.…”
contrasting
confidence: 46%
“…[1][2][3][4] Previous reports established a link between ruptured aneurysms and wall enhancement by using qualitative vessel wall MR imaging assessments. 1,5,6 However wall enhancement was also observed in unruptured aneurysms 1,6 ; thus, we hypothesized that the degree of enhancement is higher in ruptured than in unruptured aneurysms. In this study, we used a quantitative method to compare the degree of enhancement between ruptured and unruptured intracranial aneurysms by using a 3D-T1WI FSE sequence.…”
mentioning
confidence: 98%
“…A VW-MR imaging study 81 of 5 patients with aneurysmal subarachnoid hemorrhage found that all ruptured aneurysms demonstrated thick peripheral enhancement. Three patients in this series had multiple aneurysms, and the unruptured aneurysms did not enhance.…”
mentioning
confidence: 99%